Attitudes and anxieties of business and education students towards English: some data from the Basque Country. Issue 1 (2nd January 2018) - Santos, Alaitz; Cenoz, Jasone; Gorter, Durk
ABSTRACT: The aim of this article is to focus on university students' attitudes towards English and their anxieties concerning the use of English in the Basque Country, a multilingual context where exposure to English is limited but internationalisation is an important aim. Participants were 360 undergraduate university students of business ( N  = 180) and education ( N  = 180) at the University of the Basque Country. The results of the questionnaires indicate that business students had a more positive attitude(s) towards English than education students. The findings also indicate that female business students have a relatively positive attitude in comparison to male business students but also a higher level of anxiety. The results are discussed as related to the situation of English-medium instruction in Southern European bilingual areas and previous studies on gender, attitudes and anxiety.